Immunosuppressive therapy in adults with aplastic anaemia: single-institution experience from India. Issue 1055 (18th May 2013) - Nair, Velu; Sharma, Ajay; Das, Satyaranjan; Sondhi, Vishal; Sharma, Sanjeevan
Abstract : Objective: To determine overall survival and factors predicting survival after immunosuppressive therapy in patients with acquired aplastic anaemia. Design: Retrospective. Setting: Tertiary care hospital. Patients: 120 adults diagnosed as having acquired aplastic anaemia between 1 January 1996 and 31 December 2009. Interventions: Anti-thymocyte globulin (ATG) followed by ciclosporin was administered to all patients for 15–18 months as the initial treatment. Haematological response was assessed 6 months after ATG administration and 6-monthly thereafter. Platelets were transfused if levels were <10 × 10 3 /l and for symptomatic bleeding. Transfusions of red blood cells were given for haemoglobin levels <70 g/l or symptomatic anaemia. Febrile neutropenia was managed with antibiotics, with the addition of antifungal agents after 3–4 days of unresponsive fever. Granulocyte colony-stimulating factor was administered at a dose of 5 µg/kg/day (maximum 300 µg/day) subcutaneously for infective episodes. Main outcome measures: Primary outcome: overall survival. Secondary outcome: response to immunosuppressive therapy, failure-free survival, relapse and clonal evolutions. The response and relapse criteria were defined in accordance with the British Council for Standards in Haematology guidelines. Results: Overall response at 6 months after initiation of treatment was 85.8% (103/120). Overall survival at 76 months was 83.4%. Overall survival correlated with presence of response (complete response or partial response) at 6 months after ATG administration (HR=0.021, 95% CI 0.006 to 0.079, p<0.001). The occurrence of infectious complications adversely affected the overall survival (HR=5.71, 95% CI 1.22 to 26.77, p=0.027). Six patients relapsed. There were no deaths or adverse events 12 months after treatment among responders. Conclusions: In our study, overall survival was 83.4% at a median follow-up of 76 months. The two variables that significantly affected overall survival were response to therapy at 6 months and occurrence of infectious complications.